Added value of left atrial expansion index for non-invasive estimation of pulmonary capillary wedge pressure. (25th November 2020) - Genovese, D; Badano, L.P; Muraru, D; Carrer, A; Previtero, M; Ferraris, G; Tona, F; Tarantini, G; Iliceto, S; Perazzolo Marra, M
Abstract: Introduction: Right heart catheterization (RHC) is the reference technique for pulmonary capillary wedge pressure (PCWP) measurement but remains invasive. Transthoracic echocardiography (TTE) diastolic parameters (DPs) are used as non-invasive surrogates but have suboptimal accuracy. Left atrial expansion index (LAEI), describing LA reservoir function, could be used for indirectly estimate PCWP. Purpose: To evaluate the correlation between LAEI and PCWP and to compare LAEI accuracy against DPs in estimating PCWP. Methods: We retrospectively included the patients admitted to our department from 05/2015 to 02/2018 who underwent both a clinically indicated RHC and TTE within 24 hours. PCWP was obtained during RHC. DPs were measured offline and LAEI was calculated from LA maximum volume (MaxVol) and LA minimum volume (MinVol) as LAEI = [(LAMaxVol − LAMinVol) / LAMinVol)] × 100. Results: We enrolled 405 patients (left ventricular ejection fraction (LVEF)<50% n=172; PCWP>12mmHg n=209). LAEI showed a logarithmic correlation with PCWP. The log-transformed LAEI (lnLAEI) had an excellent linear correlation (r=−0.82; p<0.001) with PCWP, higher than DPs (LAMaxVoli: r=0.42; E/A: r=0.57; E/e': r=0.51; TRMaxVel r=0.17; all p<0.001). lnLAEI had the highest accuracy in identifying PCWP>12 mmHg (lnLAEI AUC 0.921, p<0.001) when compared to DPs and their association (Figure). lnLAEI showed an independent and added predictive value in estimating PCWP in a model including atrial fibrillation (Afib), heart rate (HR), LVEF, mitral regurgitation (MR), LAMaxVoli, E/A, E/e' and TRMaxVel (Table). Conclusions: LAEI is a simple parameter strongly associated with PCWP which might be used for PCWP estimation. Funding Acknowledgement: Type of funding source: None